Analisis Kemampuan Berpikir Kritis Siswa Madrasah Tsanawiyah dalam Menyelesaikan Soal pada Materi Fungsi - Suraya, Suraya; Al Kusaeri, Al Kusaeri; Hesikumalasari, Hesikumalasari (Mathematic Education Departement, State Islamic University of Mataram, 2024)
The aim of this research is to describe the critical thinking abilities of class VIII MTsN 2 Mataram students in solving questions on function material. The sample in this study was 30 students from class VIII-B. The type of research used is descriptive research with a qualitative approach. The subjects in this research were 6 students recommended by the mathematics subject observer teacher for class VIII-B at MTsN 2 Mataram. Sampling in this study used a purposive sampling technique, namely by selecting 2 students in the high category, 2 students in the medium category and 2 students in the low category according to the researcher's objectives. The data collection technique used was a written test with 2 descriptive questions and an interview. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The research results show that students who have high category critical thinking skills fulfill all indicators, namely focus, reason, inference, situation, clarity and overview. Students who have moderate critical thinking skills meet 4-5 indicators, namely reason, inference, situation, clarity and overview. Meanwhile, students who have low critical thinking skills fulfill 1-3 indicators, namely reason, inference and situation.